Legalitas Ucapan Selamat Natal Bagi Umat Islam Studi Kritis Terhadap Pemikiran Quraish Shihab Dalam Tafsir Al-Misbah - Mohammad ruslan (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2022)
Legality Derived from the word "legal" which means legal, valid according to law. While legality itself is legitimacy, legality. So "Legality" can be interpreted as a legitimacy or validity of a law based on State Law or the ideological source of a group. M. Quraish Shihab's interpretation process in legalizing the "Merry Christmas" greeting using QS. Maryam 33 through several methods including, using "Dalalah Lafadz 'Am, Syaddud dzaraI', and the rules of Maqashidul Lafdzi fiqh 'Ala Niatil Lafidz". With the latter method he interprets who is allowed or not to say "Merry Christmas". Like other contemporary commentators in interpreting the Qur'an, he also considers harmony and harmony between religious communities. None of the classical and contemporary scholars have stated that it is permissible to say "Merry Christmas" by saying that it has been approved by Al-Qur'an. The Qur'an is even recommended using the QS argument. Maryam verse 33 as used by M. Quraish Shihab in legalizing the saying. Ulama' who allow it only consider this as a form of "Mujamalah and Muhasanah" only. Because it is seen from the interpretation of the verse that none of the scholars interprets that the verse is a verse that approves the greeting of Merry Christmas, and also by looking at the history of the "Christmas" celebration. Keywords: Legality, Merry Christmas, Muslim